Analysis of Hotel and Restaurant Tax Revenue Before and During The Covid-19 Pandemic - Nurcholis, Fajar; Ningsih, Sri (Pusat P2M Politeknik Negeri Batam, 2025)
This study aims to analyze the hotel and restaurant tax revenue before and during the Covid-19 pandemic in Karanganyar District. This research employs a descriptive method with a qualitative approach. It utilizes both primary and secondary data sources. Data collection techniques involve interviews and documentation. Data analysis techniques include data condensation, data presentation, and drawing conclusions. The study is conducted at the Karanganyar District Regional Finance Agency to gather information regarding hotel and restaurant tax revenue, and it involves several key informants from hotel and restaurant businesses selected using purposive sampling method. The results of this research indicate that: (1) the number of hotels and restaurants generally increased from the year before to during the pandemic, (2) hotel and restaurant tax revenue experienced a significant growth overall, (3) the procedures for hotel and restaurant tax collection were implemented appropriately and operated smoothly, and (4) the efforts of the local government to enhance hotel and restaurant tax revenue were fairly successful.